2011
DOI: 10.3945/ajcn.110.007674
|View full text |Cite
|
Sign up to set email alerts
|

Short-term weight loss and hepatic triglyceride reduction: evidence of a metabolic advantage with dietary carbohydrate restriction

Abstract: Two weeks of dietary intervention (≈4.3% weight loss) reduced hepatic triglycerides by ≈42% in subjects with NAFLD; however, reductions were significantly greater with dietary carbohydrate restriction than with calorie restriction. This may have been due, in part, to enhanced hepatic and whole-body oxidation. This trial was registered at clinicaltrials.gov as NCT01262326.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
273
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(289 citation statements)
references
References 31 publications
(28 reference statements)
7
273
1
8
Order By: Relevance
“…However, intervention studies are needed to test a putative causal relationship between changes in ectopic lipid deposition and insulin sensitivity. Diet-induced weight loss in obese individuals is associated with reduction of fat in liver and skeletal muscle [3][4][5]. This has been linked to improved insulin sensitivity but has not been a universal finding.…”
Section: Introductionmentioning
confidence: 99%
“…However, intervention studies are needed to test a putative causal relationship between changes in ectopic lipid deposition and insulin sensitivity. Diet-induced weight loss in obese individuals is associated with reduction of fat in liver and skeletal muscle [3][4][5]. This has been linked to improved insulin sensitivity but has not been a universal finding.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss was similar between the groups. Liver TG decreased significantly with weight loss, but the reduction was more intense in the low-carbohydrate subjects compared with in the low-calorie group [60] . In order to evaluate the effects of an even more restricted carbohydrate diet (< 20 g/d of carbohydrate) on liver histology, a pilot study including 5 NAFLD obese subjects (confirmed by liver biopsy) were instructed to follow a ketogenic diet associated with nutritional supplementation for 6 mo.…”
Section: Intrahepatocellular Lipidsmentioning
confidence: 79%
“…The reduction of the ALT concentrations was associated with increasing in insulin sensitivity and decreasing in daily insulin requirement [63] . On the other hand, a 2-wk on VLCD (20 g/d) or calorie restriction (1200-1500 kcal/d) correlated with a reduction in the serum levels of AST, but not ALT, in patients with NAFLD [60] . The specific effect of a low-fructose diet was evaluated in both children and adults with NAFLD.…”
Section: Liver Enzymesmentioning
confidence: 89%
“…For example, significant reductions in hepatic triglyceride content (in excess of 50%) can be achieved within a few days of starting a low-carbohydrate diet. 30,31 Thus, using MR imaging to indirectly quantify IHF content, it may be possible to identify "high risk" patients preoperatively and initiate a low-carbohydrate diet to reduce the chances of post-resection mortality. The next platform of studies should test the reliability and reproducibility of intrahepatic fat measurement in CLM patients using non-invasive imaging and quantify reductions in triglyceride content following dietary intervention.…”
Section: Discussionmentioning
confidence: 99%